2015
DOI: 10.1007/s00259-015-3102-x
|View full text |Cite
|
Sign up to set email alerts
|

Basal 18 F-fluoro-2-deoxy-d-glucose positron emission tomography/computed tomography as a prognostic biomarker in patients with locally advanced breast cancer

Abstract: PET imaging with (18) F-FDG offers prognostic information for LABC that can be obtained preoperatively and noninvasively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Evidence level III, weak recommendation . 14,1728,3646 For more information, see Tables 4, 5, and 7.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence level III, weak recommendation . 14,1728,3646 For more information, see Tables 4, 5, and 7.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have gone as far as to correlate a lower SUV max with an improved DFS (Kadoya et al , 2013; Aogi et al , 2015; Garcia Vicente et al , 2015) and OS (Aogi et al , 2015; Garcia Vicente et al , 2015). This suggests a link between SUV max and tumour biology and/or phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorine 18 ( 18 F) fluorodeoxyglucose (FDG)–combined positron emission tomography (PET) and computed tomography (CT) (PET/CT) is based on the abnormally high rate of glucose metabolism found in cancer cells. It is widely used in diagnostic imaging of many malignant tumours [ 14 16 ]. Although previous studies showed that 18 F-FDG PET had relatively low sensitivity in the assessment of nodal status in early-stage CRC, it showed better performance than conventional imaging methods, including CT [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%